Dynamic development paths for expanding a proof‐of‐concept study to explore dose range. (21st June 2018) - Deng, Qiqi; Bai, Xiaofei; Ting, Naitee
Abstract : In Phase II clinical development of a new drug, the two most important deliverables are proof of concept (PoC) and dose ranging. Traditionally, a PoC study is designed as the first Phase II clinical trial. In this PoC, there are two treatment groups—a high dose of the study medication, against the placebo control. After the concept is proven, the next Phase II study is a dose‐ranging design with many test doses. This paper proposes a two‐stage design with the first stage attempting to generate an early signal of efficacy. If successful, the second stage will adopt a "Go Fast" plan to expand the current study and add lower study doses of the test drug to explore the efficacy dose range. Otherwise, a "Go Slow" strategy is triggered, and the study will stop at a reduced sample size with high dose and placebo only.